Review of the genus Neurigona (Diptera: Dolichopodidae) from Thailand with three new species. (2nd January 2020) - Wang, Meng-Qing; Yang, Ding; Zhang, Li-Sheng
ABSTRACT: Five species of Neurigona Rondani are known to occur in Thailand, with the following three described and illustrated: N. elongata Wang, sp. nov ., N. hauseri Wang, sp. nov ., and N. longiseta Wang, sp. nov . Neurigona concaviuscula Yang is first recorded from Thailand and a key to all species known from the country is provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:159BA6B7-534F-4F57-A549-15D166A07A11